A study to assess the effectiveness of information guide sheet on knowledge regarding impact of mobile phone use on health status among students in selected degree college at Chengalpattu District - D.Kalaimani, T.Komalavalli,R. Danasu (Forest Chemicals Review)
To assess the level of knowledge regarding impact of mobile phone use on health status among students. To develop and administer a information guide sheet on knowledge regarding impact of mobile phone use on health status among students. To assess the effectiveness of information guide sheet on impact of mobile phone use on health status among students by the posttest knowledge score. To find out the association between the pre test knowledge regarding impact of mobile phone use on health status among students with selected demographic variables such as age, gender, educational status, religion, place of resident, family income, owns a mobile, type of mobile, duration and frequency of use, and sources of information.